Reporting the Gonski Review of school funding - Shine, Kathryn (Journalism Education Association, 2016)
Issues relating to schools and schooling are regularly the subject of news reporting, yet research about news coverage of education is rare within journalism studies. This paper examines news coverage of a major educational issue in Australia: the 2012 Gonski Review of school funding. The content analysis of reporting over three years from ABC news online, The Age newspaper, The Daily Telegraph newspaper and The West Australian newspaper aimed to identify the focus of the reporting and the main sources quoted throughout. Overall, the coverage was highly political in nature. Politics was the main focus of the coverage, and federal and state politicians were the dominant sources. Principals and teachers were under-represented, and the perspectives of other key stakeholders were rarely included. These findings raise questions about the breadth of coverage of this significant public interest issue, and suggest that reporters of education are not engaging with the community they serve.